Information Management Applied to Police Sciences: a perspective of organizational culture and innovation for public safety - Filho, José Ferreira Pontes (Advanced Notes in Information Science, 2023)
Information Management (IM) has become a critical issue in supporting police forces, combating criminal organizations, and improving the performance of public security in the country. Faced with this reality, the main objective of this work is to analyze the importance of Information Management, organizational culture, and innovation processes in the environments of public security agencies as a support to the fight against crime. This research is characterized by being descriptive, where, from bibliographical research, a survey of the primary references on the approached themes was made to compile elements that facilitate obtaining the expected results for this research. Faced with the high levels of criminality organization, the implementation of GIP processes, observing the concepts brought by the theories addressed, is an alternative to boost the improvement of the provision of the public police service and, with that, the improvement of society's quality of life.